Heat shock protein 19.9 (Hsp19.9) from Bombyx mori is involved in host protection against viral infection. (January 2021) - Jiang, Liang; Xie, Enyu; Guo, Huizhen; Sun, Qiang; Liuli, Haoyu; Wang, Yumei; Li, Qing; Xia, Qingyou
Abstract: Adverse environmental conditions cause serious economic losses in sericulture; Bombyx mori nucleopolyhedrovirus (BmNPV) is the primary biotic stress and high temperature is the major abiotic stress in this industry. B. mori heat shock protein 19.9 ( Bmhsp19.9 ) overexpression was previously demonstrated to protect transgenic silkworm H19.9 against extreme temperature. This study analyzed the role of Bmhsp19.9 in H19.9A and H19.9B silkworm lines and BmE cells infected with BmNPV at regular and high temperatures. qPCR results showed that Bmhsp19.9 expression was upregulated in BmE cells and silkworm after BmNPV challenge. Bmhsp19.9 overexpression significantly inhibited BmNPV proliferation in BmE cells. The viral DNA content was significantly decreased in transgenic H19.9 silkworm compared to the control. These results suggested that Bmhsp19.9 was involved in antiviral immunity against BmNPV. Furthermore, Bmhsp19.9 overexpression protected BmE cells against BmNPV under high temperature shock. This indicates that Bmhsp19.9 is a promising candidate for improving silkworm resistance to biotic and abiotic stresses, thereby reducing sericulture losses. Highlights: Heat (atmosphere) and BmNPV infection (biosphere) significantly impact sericulture. Bmhsp19.9 expression after BmNPV and high temperature exposure was evaluated. QPCR showed that Bmhsp19.9 was induced by BmNPV infection and high temperature. Bmhsp19.9 overexpression protects against BmNPV under high temperature shock. Bmhsp19.9 is a promising candidate for improving silkworm resistance to stresses.